Osada ludności trzcinieckiego kręgu kulturowego w Lutoryżu, stan. 9 nad środkowym Wisłokiem - Adamik-Proksa, Joanna; Mazurek, Mirosław; Sznajdrowska-Pondel, Aleksandra (Muzeum Okręgowe w Rzeszowie, 2023)
The aim of the article is to present and analyse the sources of the Trzciniec culture coming from the site 9 in Lutoryż, which were obtained during archaeological excavations conducted in 2022 by ABP THOR sp. z o.o., and the Archaeological Workshop of Mirosław Mazurek. The site is part of a larger settlement cluster of the Trzciniec culture in the Rzeszów area, which has been known in the literature since 2003. The information and archaeological sources gathered in the course of the research complement and specify the knowledge about the settlement of the Trzciniec culture in this area. From the perspective of chronology and the diversity of sources, it is worth noting that considering the materials discovered at the site, they include both ceramic sources with „post-classical” stylistics as well as older materials representing the classical phase.
The settlement of the population of the Trzciniec culture in Lutoryż, site 9, on the middle Wisłok River
Keywords: Bronze Age; Trzciniec culture; classical phase; younger phase; settlement archaeology